Science in the service of society: Is marine and coastal science addressing South Africa’s needs? - Cochrane, Kevern L.; Sauer, Warwick H.H.; Aswani, Shankar (South African Journal of Science, 2019)
The modern world is confronted with many and diverse social and environmental challenges of high complexity. In South Africa, rapid and sustainable development is needed to address high levels of poverty and unemployment but this development has to take place in the context of an environment that is already severely impacted by human activities. Sound and relevant scientific input and advice, covering the full scope of each challenge, is essential for effective decisions and actions to address the needs. South Africa has the benefit of strong scientific capacity but the country’s National Development Plan reported that national research priorities were not always consistent with South Africa’s needs. We investigate the validity of that conclusion in the coastal and marine sciences by examining presentations made at the 2017 South African Marine Science Symposium on the theme of ‘Unlocking the ocean’s economic potential whilst maintaining social and ecological resilience’. Despite the theme, only 21% of the presentations were judged to be actionable and directly relevant to societal needs, as defined by the criteria used. Less than 7% were evaluated as being interdisciplinary within the natural sciences and approximately 10% were found to include both natural and human sciences. Poor representation by the human sciences was also noteworthy. This preliminary assessment highlights the need for an urgent review of the disciplinary representation and approaches in marine and coastal science in South Africa in the context of the priority practical needs of the country now and into the future. Significance: Despite the urgent need for integrated scientific input and advice to guide responsible and sustainable national development, a preliminary snapshot of marine and coastal science in South Africa demonstrated a low regard for direct relevance and inter- and multidisciplinarity. If these general results are verified by a more comprehensive review, urgent realignment of funding and incentives for marine and coastal science, and probably environmental science in general, is likely to be required to ensure science provides a greater service to society, which is the source of much of the country’s research funding. Open data set: https://sancor.nrf.ac.za/Documents/SAMSS%202017%20Congress%20Book.pdf